Pembelajaran Luas Segiempat untuk Siswa Kelas VII Menggunakan Reallotment Activities - Fitri, Nur Lailatul; Prahmana, Rully Charitas Indra (JURNAL REVIEW PEMBELAJARAN MATEMATIKA, 2018)
This research uses reallotment activities that already designed by previous research to know the role of reallotment activities in great rectangular learning. This research uses descriptive research method implemented in class 7th at SMP N 3 Banguntapan, Bantul, Yogyakarta. The data collection techniques used are documentation, observation, and test. Furthermore, the researcher analyzed the data obtained through video recording, observation, and student test answers. The results show that reallotment activities can assist students in finding the square formula by changing the shape of a rectangle into a rectangular shape. The learning activities that use reallotment activities consist of action comparing the area of ââan irregular shape, replacing the regular form into squares, determining the area of ââthe rectangle and the parallelogram, finding the formula of the breadth of the parallelogram, and also determining the area of ââthe trapezium, the parallelogram, and kite.